Особенности заболеваемости ОРВИ на участке обслуживания Джанкойской линейной санэпидстанции - Кузнецов, В.Г.; Козуля, В.К.; Козуля, С.В. (Таврический медико-биологический вестник, 2010)
Із-за контактів з потоком пасажирів працівники залізничного транспорту відносяться до групи ризику по інфекційним захворюванням з аерогенним механізмом передачі. Внесення до бюджету організацій статті витрат «на засоби профілактики інфекційних захворювань» сприяло б зниженню фінансових втрат за рахунок зменшення числа днів непрацездатності. From a contact with the stream of passengers, the workers of railway transport behave to the group of risk on infectious diseases with the aerogene mechanism of transmission. Bringing in the budget of organization article of expense «on facilities of prophylaxis of infectious diseases» would be instrumental in the decline of financial losses due to diminishing of disability days number.